Egy mezőgazdasági vállalkozás mindennapi kihívásokra adott válaszai - Tóth Katalin; Nagy Mónika Zita (2016)
Basedonthe net profit results the milk production of examined agricultural enterprise should have been eliminated a few years earlier. Does the limited company have any other motivation over economic goals? Besides achieving a profit in many cases other factors also influence the actions of a leader such as commitment to employees and loyalty. The economic changes nowadays greatly complicate the work of the farmers. It is assumed that the main purpose of the leaders, owners is to maximize profit. So the article examines and explores - beyond the concrete figures – that, how the changes in the life of an agricultural enterprise - elimination of the dairy sector and the decrease in land – affect the profitability of the enterprise and its human resources. The study is based on economic calculations and on the interviews with the agricultural enterprise’s management team. According to our results, the number of current employees exceeds the economically justified headcount.